Position Paper: Management of Men Complaining of a Small Penis Despite an Actually Normal Size. (18th April 2012) - Ghanem, Hussein; Glina, Sidney; Assalian, Pierre; Buvat, Jacques
ABSTRACT Introduction. With the worldwide increase in penile augmentation procedures and claims of devices designed to elongate the penis, it becomes crucial to study the scientific basis of such procedures or devices, as well as the management of a complaint of a small penis in men with a normal penile size. Aim. The aim of this work is to study the scientific basis of opting to penile augmentation procedures and to develop guidelines based on the best available evidence for the management of men complaining of a small penis despite an actually normal size. Methods. We reviewed the literature and evaluated the evidence about what the normal penile size is, what patients complaining of a small penis usually suffer from, benefits vs. complications of surgery, penile stretching or traction devices, and outcome with patient education and counseling. Repeated presentation and detailed discussions within the Standard Committee of the International Society for Sexual Medicine were performed. Main Outcome Measure. Recommendations are based on the evaluation of evidence‐based medical literature, widespread standards committee discussion, public presentation, and debate. Results. We propose a practical approach for evaluating and counseling patients complaining of a small‐sized penis. Conclusions. Based on the current status of science, penile lengthening procedure surgery is still considered experimental and should only be limited to special circumstances within research or university institutions with supervising ethics committees. Ghanem H, Glina S, Assalian P, and Buvat J. Position paper: Management of men complaining of a small penis despite an actually normal size. J Sex Med **;**:**–**.